ChemInform Abstract: Rhodium‐Catalyzed Oxidative Annulation of Sulfonylhydrazones with Alkenes. Issue 11 (8th March 2013) - Li, Guifei; Ding, Zhengwei; Xu, Bin
Abstract The title reaction allows a straightforward and efficient access to a number of biologically important 1, 2‐dihydrophthalazines.